Subsistence Exposure Scenarios for Tribal Applications - Harper, Barbara (2012)
The article provides an overview of methods that can be used to develop exposure scenarios for unique tribal natural resource usage patterns. Exposure scenarios are used to evaluate the degree of environmental contact experienced by people with different patterns of lifestyle activities, such as residence, recreation, or work. in 1994, U.S. President Bill Clinton's Executive Order 12898 recognized that disproportionately high exposures could be incurred by people with traditional subsistence lifestyles because of their more intensive contact with natural resources. Since then, we have developed several tribal exposure scenarios that reflect tribal-specific traditional lifeways. These scenarios are not necessarily intended to capture contemporary resource patterns, but to describe how the resources were used before contamination or degradation, and will be used once again in fully traditional ways after cleanup and restoration. The direct exposure factors for inhalation and soil ingestion rates are the same in each tribal scenario, but the diets are unique to each tribe and its local ecology, natural foods, and traditional practices. Scenarios, in part or in whole, also have other applications, such as developing environmental standards, evaluating disproportionate exposures, developing sampling plans, planning for climate change, or evaluating service flows as part of natural resource damage assessments.